Lactate: The Fallacy of Oversimplification - Müller, Jiri; Radej, Jaroslav; Horak, Jan; Karvunidis, Thomas; Valesova, Lenka; Kriz, Miroslav; Matejovic, Martin (Biomedicines, 2023)
Almost a quarter of a millennium after the discovery of an acidic substance in sour milk by Swedish chemist Carl Wilhelm Scheele and more than 100 years after the demonstration of a tight connection between this lactic acid and tissue hypoxia in shock, we are still surrounded by false beliefs and misunderstandings regarding this fascinating molecule. Common perceptions of lactate, the conjugate base of lactic acid, as a plain waste product of anaerobic metabolism and a marker of cellular distress could not be further from the truth. Lactate is formed and utilized continuously by our cells, even under fully aerobic conditions, in large quantities, and although marked hyperlactatemia is always a red flag in our patients, not all these conditions are life-threatening and vice versa-not all critically ill patients have hyperlactatemia. Lactate also does not promote acidosis by itself; it is not toxic, nor is it a metabolic renegade. On the contrary, it has many beneficial properties, and an interpretation of hyperlactatemia might be trickier than we tend to think. The aim of this article is to debunk some of the deeply rooted myths regarding this fascinating molecule.
Keywords: shock; lactic acidosis; septic shock; hyperlactatemia; hypoxia; lactate; sepsis; lactate metabolism